Introduction. Waste in Films – Waste after Films: Before the War - Kääpä, Pietari; Kaźmierczak, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
When we invited interested authors to contribute to the special issue titled “Waste in Films – Waste after Films,” we expected papers about waste shown in fictional films and in the real world, and in every potential “transitional” discursive form. In our call for papers, we sug- gested that waste is not only a metaphor, not only a sign and symbol in cinematic text, but also a material impact of film production. Waste is the visible consequence of film production, although its causes are often less visible. Waste is often treated as a political and economic challenge, but its role as the source of ecological disaster can be overlooked.